THE INFLUENCE OF RETURN ON ASSET (ROA) AND CURRENT RATIO (CR) ON BOND RATING - Ana Susi Mulyani; Wawan Ichwanudin (Management Science Research Journal, 2022)
Bond rating is something that should be considered for investors and issuers before making a decision on bond investment. This study aims to determine the effect of ROA and CR on the Rating of Bonds. The research population is non-financial sector companies listed on the Indonesia Stock Exchange in 2013-2017. The research sample amounted to 22 companies out of 453 population numbers using the Purposive Sampling method. Data analysis techniques use logistic regression. Results: 1) ROA has a positive and significant effect on bond ratings. 2) CR does not affect the bond rating.